Peningkatan Efektifitas Komunikasi Anggota Korem Wijaya Kusuma Purwokerto melalui Pelatihan Public Speaking - Ade Tuti Turistiati; Safriady Safriady (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
Members of the Indonesian National Army (TNI) in Wijaya Kusuma Military Resort Command (Korem), Banyumas, Central Java, required public speaking skills. The Commanders of the Military District (Dandim) and Information for Korem & Kodim must improve their public speaking skills and develop a strategy for dealing with media inquiries about various events or providing public information. Public speaking training is provided as a form of community service in response to these needs and goals. The training is done in an interactive manner. The participants were given the opportunity to practice public speaking on the given topic. The facilitator then provided feedback to the participants on how to improve the effectiveness of their public speaking. Aside from that, they conducted questions and answers, as well as discussions, based on the problems they faced. The training resulted in a greater understanding of public speaking strategies among the participants. They also feel more prepared and confident when confronted by the media and society.